Flipped Learning for Social Studies Instruction - Bergmann, Jonathan; Sams, Aaron (Book collections on Project MUSE., 2015)
In this book, the authors discuss how educators can successfully apply the flipped classroom model to teaching social studies. Each chapter offers practical guidance, including how to approach lesson planning, what to do with class time, and how to flip interactive social studies simulations.